Religious coping and spirituality as mediators between perceived stress and resilience in adults with type 2 diabetes mellitus - Ramírez Jiménez, María Gabriela (2022)
Background: Resilience is a psychological resource related to significant improvements in the health of people with type 2 diabetes mellitus T2DM and is linked to religious coping and spirituality and lower levels of stress. Objectives: To analyze the relationship between perceived stress and resilience as well as the direct and indirect and total effects of spirituality and religious coping through a hypothesized mediation model in people with T2DM. Method: A cross-sectional study conducted with a total of 216 participants, out of whom 41.2% were men and 58.8% were women in the age range of 30 to 78 years (M = 56.63, SD = 11.27). The Perceived Stress Scale (PSS-14), the Spirituality Scale (SS), the Religious Coping Strategies Inventory (IEAR) and the Resilience Questionnaire were used. Results: Religious coping mediates the relationship between stress and resilience by showing a significant indirect effect (β = -.05, SE = .02, 95% CI [-.09, -.01]), whereas spirituality is not a significant predictor in such relationship (β = .03, SE = .03, 95% CI [-.09, .03]). Conclusions: Evidence was found regarding the mediation effect of religious coping between perceived stress and resilience, as well as the relationship between spirituality and resilience in people with T2DM. Authorship contribution MGRJ: study design, data analysis and processing, writing of introduction, results and discussion. NIGL: study design, data analysis and processing, introduction, results and discussion. AORM: analysis and processing of data, setting up tables and figures. HOB: analysis and processing of data, configuration of tables and figures, general revision of the document in APA 7th edition format. BEBE: data analysis and processing, general revision of the document in APA 7th edition.